Quantification of litter and organic carbon in fragment of cerrado sensu stricto in Tocantins - Santana, Thiêssa Tamilla de Carvalho; Aguiar, Bruno Aurélio Campos; Teixeira, Lorena Gama; Gama, Rafaela da Costa; Santos, André Ferreira dos; Souza, Priscila Bezerra de (Scientia Agraria Paranaensis, 2020)
This study aimed to quantify the accumulated litter of a fragment of cerrado sensu stricto, besides estimating the organic carbon stored from the organic matter. We conducted the study in a sensu stricto cerrado fragment in the municipality of Formoso do Araguaia, State of Tocantins, where samples of litter were collected in six random plots of 10 m x 50 m (500m2) using a 0.5 m x 0.5 m iron template by throwing it into the ground to collect the material. We separated the collected litter into two fractions, dry and green litter. Those collected were conditioned in paper containers for oven drying at 70°C for 48 h. It was weighed 1.5 g of the biomass ground in porcelain crucibles, which were dried in an oven at 105°C for 24h, then in the muffle at 550°C for 3h, at the Madeira Laboratory from the Federal University of Tocantins. For the litter, it was quantified 4.36 t ha-1 (value below the ones found in the literature), 69.08% of organic matter for the dry material, 95.42% of organic matter for the green material, 0.546 t ha-1 of organic carbon in the dry material, 0.769 t ha-1 of organic carbon in the green material.